Pengembangan Instrumen Asesmen Higher Order Thinking Skills (HOTS) pada Mata Pelajaran Bahasa Indonesia SMA dan SMK - Sutami; Yusak Hudiyono; M. Ilyas (Magister Pendidikan Bahasa dan Sastra Indonesia, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mulawarman, 2020)
This research aims to produce a valid and reliable Indonesian language assessment instrument in form of HOTS test items and it describes the quality of HOTS test items to measure HOTS skill for the tenth grade of SMA and SMK students. This study was a research and development study adapted from Borg & Gall’s development model, including the following steps: research and information collection, planning, early product development, limited try out, revising the early product, field try out, and revising the final product. The research’s result shows that the HOTS assessment instrument in the form of HOTS test consists of 40 multiple choice items and 5 essay test items. Based on the judgment of the materials, construction, and language was valid and appropriate to be used. The reliability coefficients were 0.88 for the multiple-choice items, and 0.79 for essays. The multiple-choice items have the average difficulty 0.57 (average), the average of item discrimination 0.44 (good), and the distractors function well. The essay items have the average of item difficulty 0.60 (average) and the average of item discrimination 0.45 (good)